Peran Program Pembelajaran dalam Meningkatkan Profesionalitas Guru di Madrasah Ibtidaiyah Negeri 2 Bengkulu Selatan - Kristanti Olivia; Eem Merani Destiana (Al-Khair Journal: Management Education, 2024)
Abstract: The professionalism of teachers is still low, marked by teachers still not being able to show learning programs such as SILABUS, Semester Program Plan (RPS), Learning Program Plan (RPP), Weekly Program Plan (RPM) and Daily Program Plan (RPH). The purpose of this research is to map and analyze the role of learning programs in improving the professionalism of teachers at Madrasah Ibtidaiyah Negeri 2 South Bengkulu. Using descriptive qualitative methods, data collection techniques through observation, interviews, and documentation. Data analysis techniques using Huberman's theory. The results of the study show that the existing learning programs are not fully effective in supporting the improvement of teachers' professionalism, due to limited understanding in creating learning programs, including constraints on access to training, limited technology, and lack of coordination between stakeholders. The professionalism of teachers has not been maximized, marked by teachers who have not been able to display learning programs systematically and have not been able to develop the latest curriculum. Thus, it can be concluded that the learning program plays a role in improving the professionalism of teachers, so it can be suggested that to improve the professionalism of teachers, then increase the role of the learning program systematically in the madrasah.Keywords: Role, Learning Program, Teacher Professionalism, Madrasah Ibtidaiyah. Abstrak: Profesionalitas guru masih rendah, ditandai dengan guru-guru masih belum mampu memperlihatkan program pembelajaran seperti SILABUS, Rencana Program Semester (RPS), Rencana Program Pembelajaran (RPP), Rencana Program Mingguan (RPM) dan Rencana Program Harian (RPH). Tujuan Penelitian ini untuk memetakan dan menganalisis peran program pembelajaran dalam meningkatkan profesionalitas guru di Madrasah Ibtidaiyah Negeri 2 Bengkulu Selatan. Menggunakan metode kualitatif deskriptif, teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan teori Huberman. Hasil penelitian menunjukkan bahwa program pembelajaran yang ada belum sepenuhnya efektif dalam mendukung peningkatan profesionalitas guru, disebabkan keterbatasan pemahaman dalam membuat program pembelajaran, termasuk kendala akses pelatihan, keterbatasan teknologi, dan kurangnya koordinasi antar-stakeholder. Profesionalitas guru belum maksimal, ditandai dengan guru belum mampu menampilkan program pembelajaran secara sistematis dan belum mampu mengembangkan kurikulum terbaru. Dengan demikian dapat disimpulkan bahwa program pembelajaran berperan dalam meningkatkan profesionalitas guru, sehingga dapat disarankan bahwa untuk meningkatkan profesionalitas guru, maka tingkatkanlah peran program pembelajaran secara sistematis di madrasah.Kata kunci: Peran, Program Pembelajaran, Profesionalitas Guru, Madrasah Ibtidaiyah.